Energy harvesting from a hybrid piezo-dielectric vibration energy harvester with a self-priming circuit. (15th June 2023) - Lai, Zhihui; Xu, Junchen; Fang, Shitong; Qiao, Zijian; Wang, Suo; Wang, Chen; Huang, Zhangjun; Zhou, Shengxi
Abstract: A hybrid piezo-dielectric vibration energy harvester (PDVEH) with a self-priming circuit (SPC) is proposed and explored in this paper for passive vibration energy harvesting without an external power supply. The PDVEH consists of a piezoelectric generator (PEG) and a self-priming dielectric elastomer generator (SP-DEG). The PEG can generate electricity from its attached piezoelectric patch. The SP-DEG combines a vibro-impact DEG (VI DEG) with an improved SPC, which can gain initial charges from the PEG. The SPC then enables the DEG to charge itself using the power generated from the intermittent impacts between the inner sphere and the dielectric elastomer membranes. Hence, passive vibration energy harvesting can be realized through the PDVEH. The operation principles of both the PEG and the SP-DEG are analyzed theoretically, and the corresponding governing equations are derived. The key parameters of the PEG are identified from experimental work, and its dynamic and electrical models are verified. The passive energy harvesting process of the SP-DEG charged by PEG is verified through circuit simulations. Numerical simulations are further conducted to reveal the dynamical and electrical behaviors of the PDVEH under external excitations. It is found that the PDVEH can harvest vibration energy effectively in a low-frequency range (0–7 Hz), and its energy harvesting performance is significantly affected by the amplitude and frequency of the excitation. The maximum output power of 0.12 mW can be achieved through the PDVEH in simulations under a vibration excitation with amplitude 1.0 g and frequency 6.6 Hz, showing a potential way to realize DEG-based passive vibration energy harvesting. Highlights: A piezo-dielectric harvester is proposed for passive vibration energy harvesting. An improved self-priming circuit is used to achieve the passivity of the harvester. Governing model of the harvester is deduced for dynamical and electrical analyses. Experiments are conducted to identify parameters and verify the harvester passivity. Parametric studies provide a guideline for the harvester design and optimization.